Implementasi Budaya Organisasi dan Lingkungan Kerja dalam Meningkatkan Kinerja Karyawan pada PT. Haramein Group Bandar Lampung - Suryani (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2023)
This research aims to determine the implementation of Organizational Culture and Work Environment at PT. Haramein Group Bandar Lampung in relation to improving employee performance. The research was conducted for 6 months at the company of PT. Haramein Group Bandar Lampung ( the Umrah and Haj Plus organizing company). This type of research is qualitative descriptive. Data or information is obtained through observation and interviews with key informants and company informants as well as documentation. Based on the results of research and interviews conducted by researchers regarding the implementation of organizational culture and work environment and their relationship with employee performance at PT. Haramein Group Bandar Lampung, shows that PT. Haramein Group Bandar Lampung has implemented an organizational culture that supports improving employee performance such as cooperation in teamwork and in terms of efficiency and discipline. With the organizational culture implemented by employees at PT. Haramein Group Bandar Lampung, then makes employees very focused and disciplined because the culture implemented by the company itself greatly influences the performance of employees within the company. Proven results in achieving company goals with maximum results. Because improving the culture within the company also has an impact on creating cohesiveness within it and also a comfortable working environment within the company. Key words: organizational culture, work environment, employee performance